Low-background gamma spectrometry and neutron diffraction in the study of stony meteorites. (March 2023) - Rossini, Riccardo; Clemenza, Massimiliano; Di Martino, Daniela; Laubenstein, Matthias; Scherillo, Antonella; Musa, Maya; Riccardi, Maria Pia; Gorini, Giuseppe
Abstract: Non-destructive characterisation of meteorites is here performed on a stony meteorite. The identification of the sample is performed by low-background γ -ray spectrometry in order to determine the presence of certain cosmogenic radionuclides, whereas a mineralogical phase quantitative analysis is carried out by Time-of-Flight Neutron Diffraction (ToF-ND) on the sample as-it-is. The protocol is then validated by applying micro-Raman Spectroscopy ( μ RS) and Energy Dispersive X-ray Spectroscopy (EDS). This paper is focused on γ -ray spectrometry, proving the meteoric origin of the sample, and it also presents some preliminary results of ToF-ND. Graphical abstract: Highlights: Non-destructive characterisation of meteorites. Gamma spectrometry to identify meteorites by analysing their gamma ray emission. Time-of-Flight Neutron Diffraction to quantify mineral phases in meteorites.